Transition-Metal-Catalyzed Synthesis of Organophosphorus Compounds Involving P–P Bond Cleavage - Arisawa, Mieko (Synthesis, 2020)
Organophosphorus compounds are used as drugs, pesticides, detergents, food additives, flame retardants, synthetic reagents, and catalysts, and their efficient synthesis is an important task in organic synthesis. To synthesize novel functional organophosphorus compounds, transition-metal-catalyzed methods have been developed, which were previously considered difficult because of the strong bonding that occurs between transition metals and phosphorus. Addition reactions of triphenylphosphine and sulfonic acids to unsaturated compounds in the presence of a rhodium or palladium catalyst lead to phosphonium salts, in direct contrast to the conventional synthesis involving substitution reactions of organohalogen compounds. Rhodium and palladium complexes catalyze the cleavage of P–P bonds in diphosphines and polyphosphines and can transfer organophosphorus groups to various organic compounds. Subsequent substitution and addition reactions proceed effectively, without using a base, to provide various novel organophosphorus compounds.1 Introduction2 Transition-Metal-Catalyzed Synthesis of Phosphonium Salts by Addition Reactions of Triphenylphosphine and Sulfonic Acids3 Rhodium-Catalyzed P–P Bond Cleavage and Exchange Reactions4 Transition-Metal-Catalyzed Substitution Reactions Using Diphosphines4.1 Reactions Involving Substitution of a Phosphorus Group by P–P Bond Cleavage4.2 Related Substitution Reactions of Organophosphorus Compounds4.3 Substitution Reactions of Acid Fluorides Involving P–P Bond Cleavage of Diphosphines5 Rhodium-Catalyzed P–P Bond Cleavage and Addition Reactions6 Rhodium-Catalyzed P–P Bond Cleavage and Insertion Reactions Using Polyphosphines7 Conclusions
Keywords: P–P bond cleavage; diphosphines; polyphosphines; addition reactions; exchange reactions; insertion reactions; rhodium and palladium catalysts; organophosphorus compounds